Japanese Model of Supplier Development - Moeen Abbas (SEISENSE Journal of Management, 2018)
The supplier development was one important puzzle to be cracked for the quality revolution that was spearheaded by Japanese. But even more importantly, the bedrock of Japanese model of Supplier Development is Dr. Deming’s philosophy; the philosophy that used to seem counter intuitive before the quality revolution was realized. For instance, Dr. Deming stressed on sole supplier instead of multiple suppliers which are widely used as cushion in case any of them fails to deliver. Secondly, he reversed the nature of buyer and supplier relationship by portraying them as partners. When considered partners, gaining of one party at the expense of other and the resultant friction and dissatisfaction is uprooted in the system. Thirdly, he highlighted the importance of long term relationships with the suppliers and discarded the use of low pricing and bidding as the method of supplier selection. By studying this Japanese model of Supplier Development, I wanted to learn whether these seemingly counter intuitive principle of supplier management work. Most of the work below is derived from supplier development practices of Japanese automakers in general and Toyota and Honda in particular.